Structures for guiding and radiation of electromagnetic energy based on resonant metamaterials : doctoral thesis = Strukture za vođenje i zračenje elektromagnetske energije temeljene na rezonantnim metamaterijalima : doktorski rad - Zaluški, Davor 1984 (D. Zaluški ; Fakultet elektrotehnike i računarstva, 2013)
SUMMARY: The real parts of permittivity and permeability of most naturally occurring materials are larger than unity. That is the main reason why transversal dimension of a rectangular waveguide cannot be shorter than half of a wavelength, which prevents miniaturization of waveguide devices. However, recent theoretical and experimental results have shown that subwavelength propagation and therefore, the miniaturization, are possible when ordinary waveguides are filled with some artificial structures. These structures behave as continuous uniaxial materials with negative real parts of permeability or permittivity tensors (“Single-Negative Metamaterials”). Furthermore, recent theoretical studies revealed that specially designed artificial electromagnetic surface (“metasurface”) composed of uniaxial Epsilon-Near-Zero and Mue-Near-Zero particles behaves either as perfect electric conductor (PEC) or perfect magnetic conductor (PMC), depending on polarization of incident plane wave. This, so-called “DB” metasurface enforces vanishing of the normal components of electric and magnetic flux density vectors. In this thesis, a counter intuitive phenomenon of subwavelength propagation in a miniaturized rectangular waveguide filled with uniaxial SNG metamaterial is investigated theoretically, numerically and experimentally. Based on this analysis, several novel structures for guiding and radiation of electromagnetic energy were designed, manufactured and measured. In addition, a practical implementation of DB metasurface, based on resonant inclusions, is proposed and possible practical applications are highlighted. All achieved results are compared with the existing theoretical and experimental studies from the available literature. -